Effect of peroxydisulfate oxidation catalyzed with ordered mesoporous carbons on controlling ultrafiltration membrane fouling by algal organic matter. (September 2022) - Yun, Lei; Gao, Zhimin; Cheng, Xiaoxiang; Li, Peijie; Wang, Lin; Guo, Ning; Luo, Congwei; Zhu, Xuewu; Liu, Bin; Wu, Daoji; Liang, Heng
Abstract: As typical ordered mesoporous carbons (OMCs) materials, CMK-3 and CMK-8 were proposed for catalyzing peroxydisulfate (PDS), and the OMCs/PDS process was combined with membrane filtration to remove algal extracellular organic matter and mitigate membrane fouling. The CMK-3/PDS process achieved substantial reduction of dissolved organic carbon and UV254, followed by CMK-8/PDS. The degradation behavior of fluorescent organics demonstrated the superior performance of OMCs/PDS, while the decomposition of high molecular weight (MW) compounds and generation of lower MW organics were observed. Generally, CMK-3 possessed higher catalytic activity on PDS compared with CMK-8 and powdered activated carbon. The CMK-3/PDS process distinctly decreased the fouling resistances for polyether sulfone and polyvinylidene fluoride membranes, with the reversible resistance reduced by 59.5–83.2% and irreversible resistance declined by 71.7–73.0%. In the meanwhile, CMK-3/PDS prolonged the volumes to the transition period, and postponed the cake layer's generation. The characterization of the membrane morphologies and chemical compositions also showed effective alleviation of fouling. The generated SO4 −, OH, O2 − and 1 O2 as major active oxidation species provided radical as well as non-radical reaction ways for pollutants removal. Overall, our study provides some new ideas for membrane-based combined water purification processes. Graphical abstract: Image 1 Highlights: Ordered mesoporous carbons/peroxydisulfate (PDS) is proposed for fouling control. The removal of algal organics is promoted with catalytic PDS oxidation. A series of active species are generated in the catalytic PDS oxidation process. CMK-3 is more efficient than PAC for PDS activation and membrane fouling control. The long, straight and parallel channels contribute to the performance of CMK-3.